(untitled) (Research, Society and Development, 2021)
The oxidative stress (OS) and epigenetic changes can impact folliculogenesis in different species. In vitro culture (IVC) of follicles efficiently will require a better understanding of these events. Therefore, the objective of this review is to address the main features and advances of IVC of ovarian follicles and exposing its limitations (i.e., OS and epigenetic changes) and alternatives (i.e., antioxidants and conditioned medium of mesenchymal stem cells - CM-MSCs). In this review literature, 143 bibliographical references were used, dated from 1987 to 2021. As inclusion criteria, experimental and review literature articles and chapters were used, published in Portuguese, English and Spanish. Various researches revealed that the best results obtained by IVC of preantral follicles in mice than other species with the birth of healthy offspring. Currently, inadequate in vitro culture conditions are a potent obstacle to this biotechnology has been reported. These conditions are responsible for increased OS and changes in the epigenetic patterns of follicles (oocytes and somatic cells). Thus, to overcome this problem, different substances added into the IVC medium, such as antioxidants and media from the IVC of MSCs (i.e., CM).